ENTREPRENEURSHIP EDUCATION IN HIGHER EDUCATION: OPTIMIZING INNOVATIVE BEHAVIOUR OF Z GENERATION - Dodi Wirawan Irawanto; Khusnul Rofida Novianti (Indonesian Journal of Business and Entrepreneurship (IJBE), 2021)
Generation Z and its contribution in the formal and informal sectors are starting to appear. This is inseparable from the MSME sector, where generation Z brings a new result-oriented work pattern with the optimization of technology and information. In higher education, carrying out a response to the 4.0 industrial revolution requires universities to prepare gen Z students to adapt to this environment. This study aims to explore how the perceptions of gen Z students regarding entrepreneurship education in higher education by seeing whether it has an impact on innovative behavior. Basic research on survey research in tertiary institutions in Malang City has a mission focus on entrepreneurial spirit, namely Brawijaya University, UIN Maulana Malik Ibrahim, and the University of Muhammadiyah Malang 175 respondents and analyzed using multiple regression analysis. The result shows that entrepreneurship education with a pedagogic approach significantly affects innovative behavior, differs from the alternative approach. This research is expected to contribute to the current model of entrepreneurship education formulation. Keywords: entrepreneurship, entrepreneurship education, innovation, generation z, higher education